Manajemen strategi dan pengambilan keputusan pendidikan - Mawardi Mawardi (At Turots: Jurnal Pendidikan Islam, 2022)
Management strategy is the art and science of drafting, implementing and evaluating cross-functional decisions that can enable a company to achieve the target. Management strategy is the process of defining the organization's objectives, developing policies and plans to achieve these targets, and allocate resources to implement policies and plans to organizational objectives. Management strategy is to combine the activities of the various functional parts of a business to achieve organizational goals. Management strategy is the highest management activities are usually prepared by the board of directors and implemented by the CEO and the executive team of the organization. Management strategies provide overall direction for the company and is closely related to the field of organizational behavior. The management strategy of talking about the big picture. The essence of management is to identify the strategic goals of the organization, its resources, and how existing resources can be used most effectively to meet the objectives of the strategy in the current strategi.Manajemen should provide the basic foundation or guidelines for decision making within the organization. It is a continuous process and continuous